FAILURE OF FOLLICULAR STIMULATION AND OESTRUS INDUCTION WITH SYNTHETIC GONADOTROPIN RELEASING HORMONE AND PROGESTERONE IN DEEPLY ANOSTRUS ARABIAN MARES - F.R., ABDUL-AZIZ (The Iraqi Journal of Veterinary Medicine, 1989)
Six deeply anestrus Arabian mares associated with small, hard inactive ovaries were treated with synthetic gonadotrophin releasing hormone, GnRH, (Fertagyl ) and progesterone (Primolut Depot) to produce the gonadotrophin surges responsible for inducing follicular activity, estrus behavior and ovulation during the breeding season (Spring and Summer). The mares were given intramuscuarly three courses of the synthetic GnRH begining on days 1,11 and 21 of treatment. Each course consisted of 4 injections of 1.0 mg of Fertagyl given at 12 hours intervals. On day 23, animals were given another injection of 1.5 mg of Fertagyl, the mares also received an injections of 150 mg progesterone daily from day 5 till day 16. Clinical examination of the mares revealed neither ovarian follicular activity nor estrus behavior. It appears that synthetic GnRH and progesterone in deeply anestrus Arabian mares failed to induce cyclic follicular stimulation and estrus behavior.